PROCESS MODELLING OF K-POP CONCERT TICKETING USING BPMN: A CASE STUDY - Putri, Amanda Rahmadani; Anggraini, Umi Dwi; Baihaqi, Adrian; Huda, Muhammad Qomarul (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2025)
Abstract The Korean Wave (Hallyu) has positioned K-Pop concerts as major cultural events in Indonesia, generating economic impacts but also exposing persistent ticketing challenges. Issues such as limited supply, technical failures, lack of transparency, and fraudulent resales often lead to fan dissatisfaction. This study applies Business Process Model and Notation (BPMN) within a qualitative case study to examine and improve the ticketing workflow. Data were obtained from documentation, observation, literature review, and limited fan interviews. The current “as-is” model revealed inefficiencies including unclear digital queues, system errors, failed payments, and opaque quota distribution. A redesigned “to-be” model introduces improvements such as real-time quota visibility, One ID One Ticket enforcement, third-party purchase restrictions, and identity-based wristbands. Findings show that BPMN provides clarity of roles among stakeholders while enhancing transparency, fairness, and trust. This research demonstrates the value of process modeling for creating more reliable ticketing systems in cultural industries. Abstrak Gelombang Korea (Hallyu) menjadikan konser K-Pop sebagai peristiwa budaya besar di Indonesia yang tidak hanya berdampak ekonomi tetapi juga memunculkan berbagai kendala dalam sistem tiket. Permasalahan seperti keterbatasan kuota, kegagalan teknis, kurangnya transparansi, dan praktik penjualan ulang ilegal sering menimbulkan ketidakpuasan penggemar. Penelitian ini menerapkan Business Process Model and Notation (BPMN) dalam studi kasus kualitatif untuk menganalisis sekaligus merancang perbaikan alur kerja tiket. Data dikumpulkan melalui dokumentasi, observasi, kajian literatur, serta wawancara terbatas dengan penggemar. Analisis proses “as-is” mengungkap ketidakefisienan berupa antrian digital yang tidak jelas, kesalahan sistem, pembayaran gagal, dan distribusi kuota yang tidak transparan. Model “to-be” yang dirancang mencakup visibilitas kuota secara real-time, penerapan aturan One ID One Ticket, larangan pembelian pihak ketiga, serta distribusi gelang berbasis identitas. Hasil menunjukkan BPMN memperjelas peran pemangku kepentingan sekaligus meningkatkan transparansi, keadilan, dan kepercayaan konsumen. Penelitian ini menegaskan pentingnya pemodelan proses dalam menciptakan sistem tiket yang lebih andal di industri budaya.